2022
DOI: 10.1007/s11409-022-09301-2
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity from judgments of learning is not only due to memory forecasting: evidence from associative memory and frequency judgments

Abstract: Research has shown that judgments of learning (JOLs) often produce a reactive effect on the learning of cue-target pairs in which target recall differs between participants who provide item-based JOLs at study versus those who do not. Positive reactivity, or the memory improvement found when JOLs are provided, is typically observed on related pairs, while no reactivity is commonly found on unrelated pairs. In four experiments, we examined JOL reactivity effects by comparing JOL and no-JOL groups to other group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Similarly, other researchers have shown that the reactivity effects extend to other judgments such as judgments of forgetting (i.e., how likely are you to forget this item? ; Murphy et al 2023) and judgments of relatedness (Maxwell and Huff 2022). In a study looking at both the encoding and retrieval conditions, Chang and Brainerd (2023) found that list-level JOLs (i.e., how many items do you think you will remember from the list you just studied) enhanced free-recall, but not cued-recall, whereas item-level JOLs (as in the present experiment) enhanced cued-recall, but not free recall.…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, other researchers have shown that the reactivity effects extend to other judgments such as judgments of forgetting (i.e., how likely are you to forget this item? ; Murphy et al 2023) and judgments of relatedness (Maxwell and Huff 2022). In a study looking at both the encoding and retrieval conditions, Chang and Brainerd (2023) found that list-level JOLs (i.e., how many items do you think you will remember from the list you just studied) enhanced free-recall, but not cued-recall, whereas item-level JOLs (as in the present experiment) enhanced cued-recall, but not free recall.…”
Section: Discussionsupporting
confidence: 54%
“…In the case of related pairs, participants often use the relatedness of two words in a pair to inform their judgments (e.g., making higher judgments for related than unrelated word pairs, e.g., Koriat 1997 ). Compared to no-JOL conditions, making JOLs increases the processing of cue-target associations, which can improve performance on tests of cued recall (e.g., Halamish and Undorf 2022 ; Maxwell and Huff 2022a , 2022b ; Myers et al 2020 ; Rivers et al 2021 , 2023 ; Soderstrom et al 2015 ). Conditional analyses based on our post-experiment questionnaire, in which participants in the JOL groups were asked how they made their judgments, provide some indirect support for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our outcomes (and perhaps some of our conclusions) are limited to the specific participants, materials, encoding conditions, and retrieval conditions investigated in the current experiments. Thus, future research should continue to investigate JOL reactivity with different materials (e.g., word pairs with varying degrees of relatedness, Chang and Brainerd 2023 ; Maxwell and Huff 2022a ), method variations (e.g., self-paced versus experimenter-paced judgments, Janes et al 2018 ), different types of judgments (e.g., relatedness judgments, Halamish and Undorf 2022 ; Maxwell and Huff 2022b ), different test types (e.g., free recall or recognition; Myers et al 2020 ), and other populations (e.g., older adults, Tauber and Witherby 2019 ) for a more complete understanding of JOL reactivity across a multitude of contexts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations